Smoking during pregnancy in association with maternal emotional well-being - Giedrė Širvinskienė; Nida Žemaitienė; Roma Jusienė; Kastytis Šmigelskas; Aurelijus Veryga; Eglė Markūnienė (Medicina, 2016)
Objective: The aim of the study was to investigate psychosocial predictors of smoking during pregnancy. Materials and methods: It was a cross-sectional analysis of a prospective birth-cohort study. The participants were 514 mothers of full-term infants. Women completed questionnaires during hospital stay after delivery. Questionnaire included items on sociodemographic characteristics, planning and emotional acceptance of pregnancy, reproductive history, health-related behavior, emotional well-being, and relationships with a partner. Results: Smoking during pregnancy was reported by 14.8% of the participants. Prenatal smoking was associated with secondary or lower education, maternal age less than 20 years, childbirth outside of marriage, history of elective abortion, unplanned pregnancy, lack of positive emotional acceptance of pregnancy by mother and father, emotional distress and alcohol consumption during pregnancy. Smoking during pregnancy remained significantly associated with prenatal alcohol consumption, previous elective abortion, and lack of positive emotional acceptance of pregnancy by mother even after adjustment for maternal age, education, and family structure. Conclusions: Results support an idea of complexity of the relationships among smoking, alcohol use, and emotional well-being. Lack of positive emotional acceptance of pregnancy by mother and history of elective abortions can be considered as possible associates of smoking during pregnancy and suggest that strengthening of positive attitudes toward motherhood could add to lower smoking rates among pregnant women.